New genus and new species of Cumacea (Crustacea: Peracarida) from the mesophotic coral ecosystem of SW Puerto Rico, Caribbean Sea - Petrescu, Iorgu; Chatterjee, Tapas; Schizas, Nikolaos V. (Zootaxa, 2012)
Recent collections of the benthic macroand meiofauna associated with the mesophotic coral ecosystems of Puerto Rico haverevealed two new Cumacea from the family Nannastacidae. A new genus Cumellana and two new species, Cumellanacaribbica and Cumella alexandrinae are described herein. The new genus Cumellana can be distinguished from the other genera of the family Nannastacidae by having a long antennule and pereopod 2 with short terminal setae, equal in length.